Utilization of User Guide of Online Shopping Applications by Customers in Makassar City - Darman Fauzan Dhahir (Journal of Information Technology and Its Utilization, 2019)
The rapid growth of e-commerce is accompanied by an increase in the number of customers of application-based online store. The use of online shopping applications that are not appropriate may cause problems that result in customer losses. This quantitative research is intended to describe the utilization of online shopping application’s user guides by the customers in Makassar City. The research uses a descriptive statistic analysis. Data is displayed in the form of graphics and tables and interpreted descriptively. The results showed that the users of online shopping applications in Makassar City were less in using the user guide provided by the online shopping application provider. They preferred to do trial & error, even though they advised other users to read the tutorial. They were more concerned about convenience and simplicity than security issues. Besides, it was also found that those using the out-application-tutorials were more risked experienced problems than those did not use the tutorial at all and/or those used the in-application-tutorials.